Kinematic Performance Analysis and Scale Optimization of a Fully Symmetric 4-URU Parallel Mechanism - Yong Liu; Yong Xu; Lü Yeping; Wei Song (Jixie chuandong)
A fully symmetric 4-URU parallel mechanism with 3T1R motion is studied. Based on the screw theory, the degree of freedom of the mechanism is verified, the mathematical model of the positive and negative solution of the mechanism position is established, and the singular configuration of the mechanism is obtained. The workspace of the mechanism is solved by the numerical search method. The key scale parameters of the mechanism are optimized by examining the influence of various scale parameters on the workspace. The results of numerical calculation and motion simulation show that the kinematics model and performance analysis are correct and reasonable, and the results can provide references for mechanism mechanics analysis, structure design.